2021
DOI: 10.1162/neco_a_01363
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Decoding of Attentional States Using Closed-Loop EEG Neurofeedback

Abstract: Sustained attention is a cognitive ability to maintain task focus over extended periods of time (Mackworth, 1948; Chun, Golomb, & Turk-Browne, 2011). In this study, scalp electroencephalography (EEG) signals were processed in real time using a 32 dry-electrode system during a sustained visual attention task. An attention training paradigm was implemented, as designed in DeBettencourt, Cohen, Lee, Norman, and Turk-Browne (2015) in which the composition of a sequence of blended images is updated based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 126 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…e function looks for the pixel point as a variable, filters it, applies an edge gradient, verifies the edge, and transforms it to a width stream. Finally, the decoding algorithm extracts the QR code information, which is then sent to the storage system or display tool through RS232 connection [10][11]. Figure 4 shows the schematic design of the RS232 communication interface circuit.…”
Section: Design Of the Main Circuitmentioning
confidence: 99%
“…e function looks for the pixel point as a variable, filters it, applies an edge gradient, verifies the edge, and transforms it to a width stream. Finally, the decoding algorithm extracts the QR code information, which is then sent to the storage system or display tool through RS232 connection [10][11]. Figure 4 shows the schematic design of the RS232 communication interface circuit.…”
Section: Design Of the Main Circuitmentioning
confidence: 99%
“…The tests were selected to cover a broad range of cognitive domains and based on subgroup differences found in our previous work [ 26 ] and included: Verbal IQ (estimated based on vocabulary and similarities from WAIS-III), verbal memory (list learning from BACS), verbal fluency (F-words from BACS), mental flexibility (IED Total errors adjusted), and reaction time (RTI five choice reaction time). The features most important for the prediction were found by inspection of the feature weights estimated by the classifier [ 45 ]. The accuracy of the SVM was estimated using LOOCV.…”
Section: Methodsmentioning
confidence: 99%
“…Using electroencephalogram (EEG) sensor data, which contains electrical brain activity measured from the scalp (non-invasive) on the order of hundreds of measurements per second, many studies have established that it is possible to capture fast changes in human emotions and experience, such as stress (Perez-Valero et al, 2021), arousal (Faller et al, 2019), fatigue (Hu, 2017), and happiness (Lin et al, 2017). Several studies have similarly shown the ability to capture focus and attentional state changes, affirming that this information as well is captured in EEG sensor data (Hamadicharef et al, 2009(Hamadicharef et al, , 2009Jung et al, 1997;Micoulaud-Franchi et al, 2014;Tuckute et al, 2021). While brain decoding technology has been applied widely to study the effects of different types of stimuli (e.g visual, tactile, auditory) on human experience (Asif et al, 2019;Bhatti et al, 2016;Shahabi & Moghimi, 2016), as far as we know, it has not been applied to study the joint effects of sound and focus at the high temporal resolution needed to explain both phenomena.…”
Section: Attention and Emotion Decoding From Brain Signalmentioning
confidence: 97%